The Effect of Conventional and Digital Drawing Tools on Imagination in Architectural Design Education - Ali, Amjed M.; Himdad, Hawar (Sulaimani Journal for Engineering Sciences, 2015)
This research investigates the effects of digital drawing tools on imagination in comparison to the conventional drawing tools within the educational frame of architectural design. The significance of this study lays in the critique on the utilization of different digital drawing tools in the educational frame, seeking to find the main effects the different types of tools have on students' imagination. This study has taken imagination faculty as factor since the highest level of mental abilities is found in this specific faculty and design students cannot permit any obstacle in front of their imagination design capabilities. The problem upon which this study is based, beside the fact that the digital technology is a dialectic issue in the educational framework, its effects are also unknown as far as the students' imagination capacities are concerned. The case study involved the comparison between two groups; one group relying strongly on digital tools while the other depends merely on conventional tools, herein are students' imagination capacities as well as drawing capabilities investigated. Also the teaching staff opinions were taken from each student group by means of a questionnaire. This study has found that there is a positive relationship between drawing and imagination capabilities. And students using conventional drawing tools merely have higher imagination capabilities score as well as drawing capabilities score according to a test and evaluation form designed specifically for this study. The majority of teaching staff found that students with higher capabilities in drawing by conventional tools encompass also higher capability in imagination.
Keywords: Architectural Design; Design Imagination; Conventional Drawing Tool; Digital Drawing tool